Combined analysis of inorganic elements and flavonoid metabolites reveals the relationship between flower quality and maturity of Sophora japonica L. - Wang, Tian-Wang; Tan, Jun; Li, Long-Yun; Yang, Yong; Zhang, Xiao-Mei; Wang, Ji-Rui (Frontiers in Plant Science, 2023)
Flos Sophorae (FS), or the dried flower buds of Sophora japonica L., is widely used as a food and medicinal material in China. The quality of S. japonica flowers varies with the developmental stages (S1-S5) of the plant. However, the relationship between FS quality and maturity remains unclear. A combined analysis of the inorganic elements and flavonoid metabolites in FS was conducted to determine the patterns of FS quality formation. Sixteen inorganic elements and 173 flavonoid metabolites that accumulated at different developmental stages were identified. Notably, 54 flavonoid metabolites associated with the amelioration of major human diseases were identified, and Ca, P, K, Fe, and Cu were postulated to influence flavonoid metabolism and synthesis. This study offers a novel perspective and foundation for the further exploration of the rules governing the quality of plant materials.